Total glucosides of peony improve ovalbumin-induced allergic asthma by inhibiting mast cell degranulation. (15th November 2019) - Shou, Qiyang; Lang, Jiali; Jin, Lu; Fang, Mingsun; Cao, Beibei; Cai, Yueqin; Ni, Zhunan; Qiu, Fengmei; Li, Changyu; Cao, Gang; Fu, Huiying
Abstract: Ethnopharmacological relevance: Paeonia lactiflora Pall. (peony) is a medicinal plant used in the Xiaoqinglong decoction, a commonly prescribed traditional Chinese medicine for asthma. The main active ingredients of peony roots—described as the total glucosides of peony (TGP)—have anti-inflammatory, immunomodulatory, and protective effects on endothelial cells, and they are known to improve rheumatoid arthritis. This study explored the underlying mechanism of TGP activity in the treatment of allergic asthma. Materials and methods: Allergic asthma was induced in BALB/c mice by administering injections of ovalbumin (OVA) mixed with aluminum hydroxide gel and inhaling nebulized OVA. The OVA-sensitized mice were treated with TGP by oral gavage, and the potentially anti-asthmatic treatment effect was studied by testing airway hyperresponsiveness, classifying and counting of leukocytes, performing cytokine assays, and analyzing the lung histopathology. The β-hexosaminidase activity was assayed as a biomarker to evaluate the effect of TGP on mast cell degranulation. The mechanism of TGP was explored by monitoring the Ca 2+ influx level in mast cells (RBL-2H3) using a Ca 2+ fluorescent probe technique. Results: In mice with OVA-induced allergic asthma, TGP reduced airway hyperresponsiveness and improved lung tissue pathology, which included a decrease in inflammatory cell infiltration and collagen deposition. TGP also significantly lowered BALF leukocyte, eosinophil, and neutrophil counts, along with chemokines and cytokines, such as eotaxin, TNF-α, IL-4, and MIP-1α, in serum and lungs of OVA-challenged mice. These effects were further confirmed with the decrease of β-hexosaminidase release and the inhibition of Ca 2+ influx in mast cell degranulation. Conclusions: Our findings suggest that TGP improved OVA-induced allergic asthma in mice mainly by suppressing Ca 2+ influx-dependent mast cell degranulation. Graphical abstract: Image 1